Realization of mechanical rotation in superfluid helium - Gordon, E.B.; Kulish, M.I.; Karabulin, A.V.; Matyushenko, V.I.; Dyatlova, E.V.; Gordienko, A.S.; Stepanov, M.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
The possibility of using miniaturized low-power electric motors submerged in superfluid helium for organization of rotation inside a cryostat has been investigated. It has been revealed that many of commercial micromotors can operate in liquid helium consuming low power. Turret with 5 sample holders, assembled on the base of stepper motor, has been successfully tested in experiments on the nanowire production in quantized vortices of superfluid helium. Application of the stepper motor made it possible in a single experiment to study the effect of various experimental parameters on the yield and quality of the nanowires. The promises for continuous fast rotation of the bath filled by superfluid helium by using high-speed brushless micromotor were outlined and tested. Being realized, this approach will open new possibility to study the guest particles interaction with the array of parallel linear vortices in He II.